2020
DOI: 10.20944/preprints202001.0160.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Astrocyte Infection during Rabies Encephalitis Depends on the Virus Strain and Infection Route as Demonstrated by Novel Quantitative 3D Analysis of Cell Tropism

Abstract: Although conventional immunohistochemistry for neurotropic Rabies virus (RABV) usually shows a high preference for neurons, non-neuronal cells are also potential target cells and abortive infection of astrocytes is considered a main trigger of innate immunity in the CNS. While in vitro studies indicated differences between field and less virulent lab-adapted RABVs, a systematic and quantitative comparison of astrocyte tropism in vivo is lacking. Here, a recently developed solvent-based tissue clearing techniqu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Additionally, viral antigen has been detected in the intestine of ferrets [ 31 ], hamsters [ 34 , 35 ], and rhesus macaques [ 44 ]. Previous studies with other viral pathogens demonstrated that volumetric 3D imaging using TOC and LSFM is a highly valuable tool to assess the comprehensive distribution of virus infection in vivo [ 51 , 54 ]. Additional immunostaining against tissue-specific cell markers may further facilitate the investigation of the global SARS-CoV-2 cell tropism in affected tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, viral antigen has been detected in the intestine of ferrets [ 31 ], hamsters [ 34 , 35 ], and rhesus macaques [ 44 ]. Previous studies with other viral pathogens demonstrated that volumetric 3D imaging using TOC and LSFM is a highly valuable tool to assess the comprehensive distribution of virus infection in vivo [ 51 , 54 ]. Additional immunostaining against tissue-specific cell markers may further facilitate the investigation of the global SARS-CoV-2 cell tropism in affected tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This eliminates the need for physical sectioning and allows acquisition of intact three-dimensional (3D) structures using only optical sectioning, e.g., in light sheet fluorescence microscopy (LSFM) [ 50 ]. Lately, the opportunities and advantages of TOC for virus research have been demonstrated in several studies [ 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. While two approaches to 3D imaging of SARS-CoV-2-infected lung tissue have been described recently [ 58 , 59 ], neither of them is capable of direct visualization of SARS-CoV-2 infection via virus-specific antigen staining.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidences have shown that RABV is not a strict neurotropic virus and besides neurons it can infect other cell types 17, 18 . To comprehensively investigate the infection susceptibility of diverse cell populations and their contributions to RABV pathogenesis, we performed droplet-based scRNA-seq (10×Genomics) on a total of six mouse brain samples including two from uninfected mice (healthy: n=2), two from mice with paralysis (paralyzed: n=2) and two from mice in the moribund stage post RABV infection (moribund: n=2) (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas most of the research is focussing on the discovery of RABV receptors (1)(2)(3)(4) and their interaction with the RABV G-protein (21), less research focusses on how cellular host immune responses shape RABV tropism and how the type of response of the different neural cell types present in the CNS could collectively lead to the establishment of an antiviral response. Recently, several publications reported infection of different glial cells in vivo, particularly astrocytes (27,28) and Schwann cells (9), depending on the viral strain and the infection route used (8). Still, we are far from understanding the molecular pathways underlying susceptibility to RABV infection although it is crucial in determining infection outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Several receptors are known to accelerate RABV entry to the cell (14) and yet, none of them seems to be essential for successful infection (5,6) questioning a marked cellular tropism. Although RABV is classically reported as strictly neurotropic (7), recent studies report profound infection of glial cells in vivo depending on the viral strain and the infection route used (8,9). Here, we provide evidence that human neural stem cell (hNSC)-derived neurons (hiNeurons) and astrocytes (hiAstrocytes) are highly susceptible towards infection with the virulent field RABV strain Tha and less virulent Th2P-4M.…”
mentioning
confidence: 99%